Négocier la terre en attendant la ville: marchés fonciers et gouvernance périurbaine en Afrique subsaharienne. Issue 1 (2nd January 2023) - Bertrand, Monique; Bon, Bérénice
ABSTRACT: The fringes of sub-Saharan African metropolises are being overtaken by rapid urban sprawl, implying massive changes in land use: agricultural land, rural village land or community pastures are being converted into urban or industrial land. Studies of the processes at work remain partial. The logics of these land markets are too often restricted to mega-projects' dynamics, the restructuring of national and transnational agribusiness corporations or the centrifugal movements of city dwellers. By comparing two West and East African metropolises (Bamako and Nairobi), this article sheds light on the multiple transactions carried out on land, the various strategies of anticipation, speculation and real estate capitalization. It then analyzes how these practices are articulated with local and national political regulations of land markets. This approach allows us to propose three criteria for characterizing and classifying investments in land, in relation to urbanization dynamics in Africa.